URGENSI KEPEMIMPINAN PARTISIPATIF BAGI GURU DAN SEKOLAH - Susanto, Irwan; Reni Violina Simanjuntak; Hendri Marhadi; Mahmud Alpusari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Participative Leadership has become an important focus in modern school management due to its positive potential in enhancing teacher motivation and performance. This article aims to comprehensively explore why participative leadership is crucial for teachers and schools by reviewing both international and national literature, and by proposing a conceptual framework that connects participative leadership, teacher motivation, and school performance. The method used is a systematic literature review complemented by conceptual analysis to integrate recent empirical and theoretical findings. The results indicate that leadership which involves teachers in decision-making, grants professional autonomy, and fosters open communication helps strengthen teachers’ sense of ownership, trust, and commitment to their schools. Furthermore, this leadership style is closely associated with improved teacher performance—reflected in innovative teaching practices, inter-teacher collaboration, and professional productivity—which ultimately contributes positively to overall school quality. Schools that adopt participative leadership tend to create a more conducive and adaptive working environment in the face of change. This article recommends that school principals and educational leaders cultivate a culture of participation and develop institutional structures that support collaboration.